Identification and verification of vascular cell adhesion protein 1 as an immune-related hub gene associated with the tubulointerstitial injury in diabetic kidney disease. Issue 1 (1st January 2021) - Jia, Yan; Xu, Hui; Yu, Qi; Tan, Lishan; Xiong, Zuying
ABSTRACT: Diabetic kidney disease (DKD) is the leading cause of chronic kidney disease (CKD) and end-stage renal disease (ESRD), but the pathogenesis is not completely understood. Tubulointerstitial injury plays critical roles in the development and progression of DKD. The present study aimed to investigate the profile of tubulointerstitial immune cell infiltration and reveal the underlying mechanisms between tubular cell injury and interstitial inflammation in DKD using bioinformatics strategies. First, xCell analysis identified immune cells displaying significant changes in the DKD tubulointerstitium, including upregulated CD4 + T cells, Th2 cells, CD8 + T cells, M1 macrophages, activated dendritic cells (DCs) and conventional DCs, as well as downregulated Tregs. Second, pyroptosis was identified as the main form of cell death compared with other forms of programmed cell death. Vascular cell adhesion protein 1 (VCAM1) was identified as the top ranked hub gene. The correlation analysis showed that VCAM1 was significantly positively correlated with pyroptosis and infiltrated immune cells in the tubulointerstitium. Upregulation of VCAM1 in the DKD tubulointerstitium was further verified in European Renal cDNA Bank cohort and was observed to negatively correlate with the glomerular filtration rate (GFR). Our in vitro study validated increased VCAM1 expression in HK-2 cells under diabetic conditions, and pyroptosis inhibition by disulfiram decreased VCAM1 expression, inflammatory cytokine release and fibrosis. In conclusion, our study identified upregulated VCAM1 expression in renal tubular cells, which might interact with infiltrated immune cells, thus promoting fibrosis. The FDA-approved drug disulfiram might improve fibrosis in DKD by targeting tubular pyroptosis and VCAM1 expression.